Trends in Tuberculosis in Taiwan, 2002–2008 - Hsiu-Yun Lo; Pesus Chou; Shiang-Lin Yang; Cheng-Yi Lee; Hsu-Sung Kuo (Journal of the Formosan Medical Association, 2011)
Tuberculosis (TB) remains an important infectious disease in Taiwan. To control TB effectively, the Taiwan Centers for Disease Control implemented the National Tuberculosis Program (NTP) in 2006, modeled on the World Health Organization global TB control program. The goal of the program was to reduce the number of TB cases by half within a decade. This study was designed to describe the epidemiology of TB in Taiwan, and to evaluate the preliminary effectiveness of the NTP. Methods: We conducted a retrospective study of data from the National Tuberculosis Registry System collected between 2002 and 2008. Demographics, geographic distribution of disease, and change in rates of TB incidence and mortality were analyzed. Results: From 2002 to 2008, new TB cases declined from 16,758 to 14,265, and incidence decreased from 75 per 100,000 population to 62 per 100,000 population. More than 50% of new cases occurred among elderly adults. Over the study period, TB mortality decreased from 5.7 per 100,000 population to 3.3 per 100,000 population, with over half of TB deaths occurring among patients aged ≥ 65 years. Since the NTP was implemented, from 2005 to 2008, TB incidence and mortality declined by 14% and 23%, respectively. Conclusion: TB-associated incidence and mortality decreased over the course of the study. Nevertheless, there continue to be high-incidence areas that show the opposite trend; these areas should strive to improve case management and consultation. In the most populous districts, rigorous surveillance is necessary to track incidence and mortality rate fluctuations.